3.2k views
2 votes
5p + 9c = p for c

Help out with this problem

User Shard
by
6.2k points

2 Answers

6 votes

Answer:

Explanation:

5p + 9c = p

9c = p - 5p

9c = -4p

c = -4p/9

c=
(-4p)/(9)

User Roman Yakoviv
by
5.5k points
5 votes

SOLVING

=================================================================

First you need to subtract by 5P both sides

9c=p-5p

and combine like terms.

9c=-4p

Next divide 9 to both sides


c=(-4p)/(9)


c=-(4p)/(9)

Learn more;work harder

#Carryonlearning

==============================================================

User Skaldesh
by
5.9k points